Preliminary characterization of gut mycobiome enterotypes reveals the correlation trends between host metabolic parameter and diet: a case study in the Thai Cohort - Mok, Kevin; Poolsawat, Thitirat; Somnuk, Surasawadee; Wanikorn, Bandhita; Patumcharoenpol, Preecha; Nitisinprasert, Sunee; Vongsangnak, Wanwipa; Nakphaichit, Massalin (Scientific reports, 2024)
The association between the gut mycobiome and its potential influence on host metabolism in the Thai Cohort was assessed. Two distinct predominant enterotypes, Saccharomyces (Sa) and Aspergillus / Penicillium (Ap/Pe) showed differences in gut mycobiota diversity and composition. Notably, the Sa enterotype exhibited lower evenness and richness, likely due to the prevalence of Saccharomyces , while both enterotypes displayed unique metabolic behaviors related to nutrient metabolism and body composition. Fiber consumption was positively correlated with adverse body composition and fasting glucose levels in individuals with the Sa enterotype, whereas in the Ap/Pe enterotype it was positively correlated with fat and protein intake. The metabolic functional analysis revealed the Sa enterotype associated with carbohydrate metabolism, while the Ap/Pe enterotype involved in lipid metabolism. Very interestingly, the genes involved in the pentose and glucuronate interconversion pathway, such as polygalacturonase and l -arabinose-isomerase, were enriched in the Sa enterotype signifying a metabolic capacity for complex carbohydrate degradation and utilization of less common sugars as energy sources. These findings highlight the interplay between gut mycobiome composition, dietary habits, and metabolic outcomes within the Thai cohort studies.